2020
DOI: 10.1038/s41598-020-62739-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic disturbance in hippocampus and liver of mice: A primary response to imidacloprid exposure

Abstract: Imidacloprid (IMI) is one of the most frequently used neonicotinoid insecticides, but recent studies have shown adverse effects on mammals. IMI was found to be neurotoxic and hepatotoxic. In the present study, the effects of repeated oral administration of two doses of IMI (5 and 20 mg/kg/day) for 28 days on hippocampus and liver of female KM mice were studied. The histopathological and biochemical experiments indicated obvious damages to the hippocampus and liver of mice in the high-dose group (20 mg/kg/day).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 57 publications
2
18
1
Order By: Relevance
“…In addition, the risk of exposure to the imidacloprid was also increased by maternal exposure on organogenesis critical period. These results are in consistent with the data reported that there was a significant decrease in the body weight gain of mice in the high dose group of 20 mg/kg/day (Zheng, et al, 2020). In similar, significant toxic symptoms, together with significant decrease in weight gain appeared in rats exposed to 20 mg/kg/day of IMI (Kapoor, et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the risk of exposure to the imidacloprid was also increased by maternal exposure on organogenesis critical period. These results are in consistent with the data reported that there was a significant decrease in the body weight gain of mice in the high dose group of 20 mg/kg/day (Zheng, et al, 2020). In similar, significant toxic symptoms, together with significant decrease in weight gain appeared in rats exposed to 20 mg/kg/day of IMI (Kapoor, et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Conditions of oxidative stress and neuroinflammation, mitochondrial damage, alterations in neurotransmitter systems, as well as changes in energy metabolism induced by NN pesticides can eventually lead to neuronal death. Some of the studies included here agree that both acute and chronic treatment with IMI and ACE pesticides caused DNA damage and neuronal degeneration, especially affecting the hippocampus [15,60,70,112,155].…”
Section: Induction Of Apoptosissupporting
confidence: 56%
“…It has also been shown that exposure to NN pesticides decreased neurogenesis in the dentate gyrus of the hippocampus and promoted apoptosis in this brain structure [66,111,112]. The dentate gyrus is one of the few brain areas where neurogenesis continues to occur during adulthood [113].…”
Section: Effects On Behavior and Cognitive Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the aminoacyl‐tRNA biosynthesis and steroid hormone biosynthesis pathways, ‐log(p) > 2 and pathway impact < 0.1 indicated that pathway interference is limited. For the phenylalanine, tyrosine, and tryptophan biosynthesis and phenylalanine metabolism pathways, ‐log(p) > 2 and pathway impact > 0.1 indicate strong pathway interference, suggested that PLR effects liver function, mainly via the inhibition of the conversion of phenylalanine to tyrosine and tryptophan or the inhibition of phenylalanine metabolism (Xu et al., 2012; Zheng et al., 2020).…”
Section: Resultsmentioning
confidence: 99%